Flexible PVC materials grafted with castor oil derivative containing synergistic flame retardant groups of nitrogen and phosphorus - Jia, Puyou (Sci Rep, 2019)
Internally plasticized PVC by replacement of chlorine with castor oil derivative containing synergistic flame retardant groups of nitrogen and phosphorus, that is, castor oil derivative grafted onto PVC matrix, is reported. Low glass transition temperature (Tg) of modified PVC was produced although thermal stability was reduced. However, the migration was completely suppressed. The combination of castor oil derivative containing synergistic flame retardant groups of nitrogen and phosphorus with PVC matrix through modifying PVC materials with click reaction prepared flexible PVC materials with zero migration and enhanced flame retardant property.